Fabric, cellular and molecular interactions in a mucous membrane of bronchial at a heavy bronchial asthma - Ye. A. Gereng; I. V. Sukhodolo; R. I. Pleshko; I. V. Milto; L. M. Ogorodova; O. S. Kobyakova; Р. А. Selivanovа (Бюллетень сибирской медицины, 2012)
The complex histologic, immunogictochemic, electronic-microscopic estimation biopsiа mucous membrane of bronchial in 87 patients with heavy sensitive and therapeutic resistant bronchial asthma. It is established, that weighting of a bronchial asthma is characterised by high indicators of functional activity of corpulent cages and ultrastructural signs of strengthening secretions processes in bocalotia mucous membrane of bronchial. Therapeutic resistant bronchial asthma of a phenotype «brittle» differs development of the Th2-dependent immune answer with eosinohyils an inflammation, ultrastructural a dyskinesia resnitch epitels. A therapeutic resistant bronchial asthma of a phenotype «the asthma with the fixed bronchial obstruction» neutrophil inflammation, is accompanied a mucous membrane of bronchial tubes with a thickening basals membranes, height decrease epitels a layer with a degeneration epithelium and strengthening of an expression of receptors to the transforming factor of growth β1.